Food insecurity measurement and indicators - Pérez-Escamilla,Rafael (2008)
The United Nations define food security as "People having at all times, physical, social and economic access to sufficient, safe and nutritious food which meets their dietary needs and food preferences for an active and healthy life." There are five methods that are commonly applied in national surveys that can be used to assess food insecurity. Of these, four are indirect or derivative measures of food insecurity (United Nations Food and Agriculture Organization method, household expenditure surveys, dietary intake assessment and anthropometry). The only method that represents a fundamental or direct measure of food insecurity is the one based on experience-based food insecurity scales. All the methods complement each other and the method of choice depends on the question being answered and the economic and logistical resources available to collect valid data. All the methods have serious measurement error issues that can be reduced by fully understanding the principles underlying them and the use of highly trained and standardized research field workers. As shown in Brazil, the use of experience-based food insecurity measurement scales for mapping, targeting, and understanding the determinants and consequences of food insecurity is very promising. Thus, we recommend the Latin American and Caribbean Region to work towards the adoption of a single regional module that can be adapted to the local contexts based on qualitative cognitive research followed by quantitative confirmation of the scale's psychometric properties. The Brazilian experience-based food insecurity measurement project is likely to provide useful insights to other countries in the region.